Radiotracers for Cardiac Sympathetic Innervation: Transport Kinetics and Binding Affinities for the Human Norepinephrine Transporter - Raffel, David M. (2013)
INTRODUCTION: Most radiotracers for imaging of cardiac sympathetic innervation are substrates of the norepinephrine transporter (NET). The goal of this study was to characterize the NET transport kinetics and binding affinities of several sympathetic nerve radiotracers, including [(11)C]-(−)-meta-hydroxyephedrine, [(11)C]-(−)-epinephrine, and a series of [(11)C]-labeled phenethylguanidines under development in our laboratory. For comparison, the NET transport kinetics and binding affinities of some [(3)H]-labeled biogenic amines were also determined. METHODS: Transport kinetics studies were performed using rat C6 glioma cells stably transfected with the human norepinephrine transporter (C6-hNET cells). For each radiolabeled NET substrate, saturation transport assays with C6-hNET cells measured the Michaelis-Menten transport constants K(m) and V(max) for NET transport. Competitive inhibition binding assays with homogenized C6-hNET cells and [(3)H]mazindol provided estimates of binding affinities (K(I)) for NET. RESULTS: K(m), V(max) and K(I) values were determined for each NET substrate with a high degree of reproducibility. Interestingly, C6-hNET transport rates for ‘tracer concentrations’ of substrate, given by the ratio V(max)/K(m), were found to be highly correlated with neuronal transport rates measured previously in isolated rat hearts (r(2) = 0.96). This suggests that the transport constants K(m) and V(max) measured using the C6-hNET cells accurately reflect in vivo transport kinetics. CONCLUSION: The results of these studies show how structural changes in NET substrates influence NET binding and transport constants, providing valuable insights that can be used in the design of new tracers with more optimal kinetics for quantifying regional sympathetic nerve density.